Resistance Training and Older Adults with Type 2 Diabetes Mellitus: Strength of the Evidence. (4th September 2012) - Hovanec, Nina; Sawant, Anuradha; Overend, Tom J.; Petrella, Robert J.; Vandervoort, Anthony A.
Abstract : Objective . This paper analyzes the effects of resistance training (RT) on metabolic, neuromuscular, and cardiovascular functions in older adults (mean age ≥ 65 years) with type 2 diabetes (T2DM). Research Design and Methods . A systematic review conducted by two reviewers of the published literature produced 3 records based on 2 randomized controlled trials that assessed the effect of RT on disease process measures and musculoskeletal/body composition measures. Statistical, Comprehensive Meta-Analysis (version 2) software was used to compute Hedge's g, and results were calculated using the random effects model to account for methodological differences amongst studies. Results . Largest effect of RT was seen on muscle strength; especially lower body strength, while the point estimate effect on body composition was small and not statistically significant. The cumulative point estimate for the T2DM disease process measures was moderate and statistically significant. Conclusions . RT generally had a positive effect on musculoskeletal, body composition, and T2DM disease processes measures, with tentative conclusions based on a low number of completed RCTs. Thus, more research is needed on such programs for older adults (≥65 years) with T2DM.